2017
DOI: 10.17582/journal.ape/2017/5.1.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect of Achillea fragrantissima Against Benzene-Induced Skin Irritation: Histological Study

Abstract: | Organic solvents such as car fuel, which contains benzene and other solvents were known to cause skin irritation and contact dermatitis. Although anti-inflammatory steroids topical medications were used, they may result in side effects in susceptible persons. Herbal preparation was tried in literature. In the present study, Achillea fragrantissima, a wild plant in some areas of Saudi Arabia was used to speed slow-healing wounds. Thus, the study was designed to investigate its efficacy to treat experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…In addition, there was a significant increase in the area percent of Masson-stained collagen fibers in the dorsal skin of rats of this group compared to the control group. These observations were in line with those previously described by Alshathly and Alqahtani 2017[ 28 ] in rats painted with benzene for 3 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there was a significant increase in the area percent of Masson-stained collagen fibers in the dorsal skin of rats of this group compared to the control group. These observations were in line with those previously described by Alshathly and Alqahtani 2017[ 28 ] in rats painted with benzene for 3 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…The morphological and histopathological alternations observed in CD in this study were in accordance with those observed by Zhou et al (2016) in dinitrochlorobenzene-induced allergic CD in BALB/c mice (Alshathly and Alqahtani, 2017) in benzene-induced skin irritation in rats and (Qu et al, 2019) in oxazolone-induced CD in mice. Significant upregulation of Cox-2 immunoexpression in CD was among the findings recorded in this study and previous studies (Chang et al, 2018).…”
Section: Discussionsupporting
confidence: 89%